Pembelajaran Berbasis E-Learning di Madrasah Dalam Peningkatan Kualitas Pendidikan: Kasus MTsN Al Azhar - Ahmad, Abdul Kadir; Sumarni; Rahayu, Kun Mardiwati; Lisnawati, Santi (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2023)
Madrasah should seize the opportunities offered by E-learning to enhance the quality of education and prepare students for the digital era. E-learning in the age of digitalization has proven to be an effective alternative in providing accessibility and flexibility in learning. This research aims to investigate and analyze the strategies of E-learning implemented in madrasah, with a focus on the case of MTsN Al Azhar. The study utilizes a qualitative approach with a case study method. Data collection techniques include interviews, observations, and document studies. The analysis techniques employed involve three processes: data reduction, data display, and conclusion drawing. The research findings indicate that 1). the madrasah has successfully adopted and implemented E-learning strategies. 2). The implementation of E-learning in MTsN Al Azhar has several advantages, such as flexible accessibility for students, increased student engagement and participation in learning, and access to a wider range of learning resources through digital platforms. 3). The strategies employed by the madrasah head in implementing E-learning include the development of plans and visions, resource development, involvement of teachers and education personnel, establishment of an E-learning Management team, and collaboration with madrasah stakeholders. 4). However, there are challenges to overcome, including limited technology infrastructure, teacher readiness in adopting technology, and managing online interactions between teachers and students.